Faktor-Faktor yang Memengaruhi Revaluasi Aset Tetap pada Perusahaan Manufaktur - Teresa Livia; Sufiyati (Jurnal Ekonomi, 2022)
The purpose of this study is to determine the effect of company’s growth, fixed asset intensity, company size, operating cash flow, and leverage to fixed asset revaluation in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period of 2018-2020. This study tested the classical assumption, namely the multicollinearity test before testing the hypothesis using logistic regression analysis techniques. This study used 444 data obtained from 148 manufacturing companies that have met the established criteria. The data then inputted and calculated using Microsoft Excel and processed using the SPSS version 24 program. The results of this study indicate that company growth and operating cash flow have no significant effect and positive effect on fixed assets revaluation, fixed asset intensity has a significant and positive effect on fixed assets revaluation, and firm size and leverage have no significant and negative effect on fixed assets revaluation.